Abnormalities of P300 before and after antidepressant treatment in depression: an ERP-sLORETA study. Issue 3 (7th February 2018) - Zhou, Lina; Wang, Gaohua; Wang, Huiling
Abstract : Despite a wide range of reports on depression-induced P300 changes, it is still debatable whether P300 can return to a pattern characteristic of healthy individuals following antidepressant treatment. Thus, the present study aims to compare P300 and its underlying neural activation in depressed patients before and after antidepressant treatment to explore the brain regions related to pathogenesis and to evaluate the prognosis after treatment. P300 was evoked by the oddball auditory paradigm and collected from 14 sex-matched, age-matched, and education level-matched patients and controls. P300 was also collected in the same patients after treatment. sLORETA was used to explore the source activation of P300 components. Depressed patients before and after antidepressant treatment tended to show lower P300 amplitudes compared with healthy controls, and their P300 amplitudes of F3 electrodes were correlated negatively to their scores on the 24-item Hamilton Depression Rating Scale, the Snaith-Hamilton Pleasure Scale, and the nine-item Patient Health Questionnaire. P300 amplitudes of P4 electrodes were correlated negatively with their scores on the Dysfunctional Attitude Scale. P300 source activation of depressed patients before antidepressant treatment was reduced in the left superior parietal lobule and the precuneus compared with healthy controls and depressed patients after treatment. No difference was found between healthy controls and depressed patients after treatment. The left superior parietal lobule and the precuneus might be therapeutic targets of depression.